Early weakening processes inside thrust fault. Issue 7 (14th July 2015) - Lacroix, B.; Tesei, T.; Oliot, E.; Lahfid, A.; Collettini, C.
Abstract: Observations from deep boreholes at several locations worldwide, laboratory measurements of frictional strength on quartzo‐feldspathic materials, and earthquake focal mechanisms indicate that crustal faults are strong (apparent friction μ ≥ 0.6). However, friction experiments on phyllosilicate‐rich rocks and some geophysical data have demonstrated that some major faults are considerably weaker. This weakness is commonly considered to be characteristic of mature faults in which rocks are altered by prolonged deformation and fluid‐rock interaction (i.e., San Andreas, Zuccale, and Nankai Faults). In contrast, in this study we document fault weakening occurring along a marly shear zone in its infancy (<30 m displacement). Geochemical mass balance calculation and microstructural data show that a massive calcite departure (up to 50 vol %) from the fault rocks facilitated the concentration and reorganization of weak phyllosilicate minerals along the shear surfaces. Friction experiments carried out on intact foliated samples of host marls and fault rocks demonstrated that this structural reorganization lead to a significant fault weakening and that the incipient structure has strength and slip behavior comparable to that of the major weak faults previously documented. These results indicate that some faults, especially those nucleating in lithologies rich of both clays and high‐solubility minerals (such as calcite), might experience rapid mineralogical and structural alteration and become weak even in the early stages of their activity. Key Points: Microstructural characterization of an incipient thrust fault Fault zone is affected by a large calcite departure compared to host sediments Fault frictional strength very low even if fault experienced low displacement